2021
DOI: 10.3390/nano11112968
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Advances in Nanoparticle-Driven Stabilization of Liquid-Crystalline Blue Phases and Twist-Grain Boundary Phases

Abstract: Recent advances in experimental studies of nanoparticle-driven stabilization of chiral liquid-crystalline phases are highlighted. The stabilization is achieved via the nanoparticles’ assembly in the defect lattices of the soft liquid-crystalline hosts. This is of significant importance for understanding the interactions of nanoparticles with topological defects and for envisioned technological applications. We demonstrate that blue phases are stabilized and twist-grain boundary phases are induced by dispersing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 112 publications
(214 reference statements)
0
5
0
Order By: Relevance
“…Torons were created by using laser tweezers with a power of 100 mW, as described in refs. [11,12,21]. After generation, the torons were optically manipulated with the laser tweezers at a lower power of the order of 10 mW, remaining stable when spatially translated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Torons were created by using laser tweezers with a power of 100 mW, as described in refs. [11,12,21]. After generation, the torons were optically manipulated with the laser tweezers at a lower power of the order of 10 mW, remaining stable when spatially translated.…”
Section: Methodsmentioning
confidence: 99%
“…The utilized laser tweezer setup was built around an inverted optical microscope (IX-81, Olympus) and also comprised a 1064 nm ytterbium-doped fiber laser (YLR-10-1064, IPG Photonics) and a phaseonly spatial light modulator (P512-1064, Boulder Nonlinear Systems), in addition to various lenses and other optical elements described in detail elsewhere. [11,12,21] In some cells, torons were further controlled by applying a 1 kHz AC sinusoidal voltage across the gap between ITO glass substrates using a function generator (DS345, Standford Research Systems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the properties of the LC-host are primarily affected by the geometry of the NPs (size, shape), their bulk and/or surface properties, and their concentration. Over the past two decades, numerous theoretical and experimental studies have been appeared regarding the influence of NPs on phase transitions, orientational order, and the response of the host liquid crystalline matrix to external fields [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Naturally, the well-known Fréedericksz transition has been studied too in certain soft-nanocomposite materials for the voltage threshold of this transition is crucial for applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the last few decades, a lot of efforts have been made into the stabilisation of BP for making them appealing for application in optoelectronics or photonic sensing. To stabilise the structural features of BPs, and thereby widening the temperature range, different approaches have been followed like the introduction of polymers 11c and nanoparticles (NPs), 14 or by doping with low-molecular weight additives. 15 Polymer stabilisation was first reported by Kikuchi et al who could achieve a BP temperature range of more than 60 °C.…”
Section: Introductionmentioning
confidence: 99%